Pilates for breast cancer: A systematic review and meta-analysis - Espíndula,Roberta Costa (2017)
Summary Introduction: Breast cancer is the leading type of cancer causing death in women worldwide. The incidence of the disease is expected to grow worldwide due to the aging of the population and risk factors related to lifestyle behaviors. Considering the lifestyle of women with breast cancer before or after surgery, pilates exercise may be a complementary intervention additionally to standard treatment. Objective: To analyze the efficacy of pilates compared to other exercises and to no exercise for women with breast cancer diagnosis. Method: We searched Medline via Pubmed, Embase via Ovid, Amed via EBSCO, Biosis via Ovid, Lilacs and the Cochrane Library for relevant publications until March 2017. The keywords used were pilates and “breast cancer,” and only randomized controlled trials were included. Critical appraisal was done using Risk of Bias Tool and GRADE score for assessing the quality of evidence. Results: A total of five studies were included in our review. Our results demonstrate that pilates or home-based exercises are better than no exercise in each individual study. We observed significant improvements in the pilates groups compared to home-based exercises. Additionally, in the individual studies, we observed improvements in range of motion, pain and fatigue. Conclusion: The evidence shows that pilates or home-based exercise should be encouraged to women with breast cancer.